Effects of silver nanoparticles to the freshwater snail Physa acuta: The role of test media and snails' life cycle stage - Gonçalves, S; Pavlaki, M; Lopes, R; Hammes, J; Gallego-Urrea, J; Hassellöv, M; Jurkschat, K; Crossley, A; Loureiro, S (Wiley, 2016)
Silver nanoparticles (AgNP) are highly used worldwide, which will most likely lead to their release to the environment and subsequently increase environmental concentrations. Therefore studying AgNPs' deleterious effects to organisms is crucial to understand their environmental impacts. The freshwater snail Physa acuta was chosen to evaluate the potential deleterious effects of AgNP and counterpart AgNO3 , through water only exposures. AgNPs' toxicity is greatly influenced by medium composition. Thus, two test media were tested: Artificial Pond Water (APW) and modified APW (modified by removing calcium chloride from medium). Acute tests (96h) were performed with juvenile and adult snails, in both media, to assess lethality, and egg mass chronic tests, with APW medium only, to assess embryo viability and mortality, carried out until reaching 90% hatching success in the control. Acute toxicity increased with decreasing shell length for both silver forms (ion and nanoparticle), i.e. juveniles where more sensitive than adults. Different test media led to dissimilar LC50 values, with chloride playing an important role in toxicity, most probably by complexation with silver ions and thus reducing silver's bioavailability, uptake and toxicity. Chronic tests showed that hatching success was more sensitive to silver in the ionic form than in the particulate form. Different forms of silver, exposure media and life cycle stages led to different patterns of toxicity, highlighting an impairment in the snails' life cycle. This article is protected by copyright. All rights reserved.